“Se eu quisesse crescer na vida, eu estudava de manhã”: o projeto didático de gênero como proposta metodológica para ensino de língua portuguesa no ensino médio noturno - Pereira, Tamires Puhl (Universidade do Vale do Rio dos Sinos, 2021)
From the premise that the teaching of writing is a process that must be assisted in all stages of schooling, this research investigates how the Genre Education Project (PDG), as a methodological option, can contribute to the teaching practices of text production in Portuguese Language classes. Having as a starting point a discussion about the work with written text production in the final stage of Basic Education (BUNZEN, 2006; CORTI; MENDONÇA, SOUZA, 2012; GERALDI, 1991; PEREIRA, 2001), this study is anchored to the theoretical-methodological contributions on language and human development of Sociodiscursive Interactionism (ISD) (BRONCKART, 1999; 2006) and on teaching by text genres (text-mediated teaching) (DOLZ; SCHNEUWLY, 2004; DECÂNDIO; DOLZ; GAGNON, 2010). It is also in line with the principles outlined by Guimarães and Kersch (2012; 2014; 2015), which assume an interactionist conception of language when developing the PDG as a methodological proposal for Portuguese Language teaching. Adopting research-action as a methodology of research (FRANCO, 2005; PIMENTA, 2005; TRIPP, 2005), the data were generated from the development of a PDG in a third year class, during the night, in the High School, of a public school in the metropolitan region of Porto Alegre/RS. Considering the notions of textuality, the mechanisms of textualization (BRONCKART, 1999; MARCUSCHI, 2008; ELIAS; KOCH, 2018) and the writing skills evaluated at the writing stage of the National High School Exam (Enem) (BRASIL, 2019), an attempt was made to analyze the textual productions of students comparing the versions produced (initial version, final version and rewriting) in order to measure the development of writing in the work with textual production throughout the development process of the PDG proposed for this research. The results suggest that the textuality criteria, the textualization mechanisms and the criteria foreseen in the writing skills evaluated in the writing stage of the Enem were activated/developed in the texts produced by the students during the PDG development process, and that the teaching workshops, approached from the difficulties evidenced in the diagnostic version of the text, contributed to a progressive development in the rewriting version in relation to the writing difficulties presented in the first production, evidencing the relevance of the work with PDG in the teaching of writing in a High School in classes during the nigh.
Keywords: Ensino médio; Ensino de escrita; Gêneros de texto; Projeto didático de gênero; High school; Teaching writing; Text genres; Genre education project; ACCNPQ::Lingüística, Letras e Artes::Lingüística